Reproductive Health Education Needs Among Adolescents and Young Adults: A Community-Based Survey - Susanto, Shobri Firman; Mardliyah, Sjafiatul; Susilo, Heryanto; Widodo, Widodo; Widyaswari, Monica (Journal of Nonformal Education, 2026)
Background – The need for reproductive health education among adolescents and young adults is influenced by social conditions, parenting styles and family communication, perceptions of reproductive health, peer relationships, as well as social and information environments.Research Urgency – Reproductive health education needs to be grounded in actual requirements to ensure that developed programs align with the characteristics and life contexts of the target group.Research Objectives – This study aims to analyze the reproductive health education needs of adolescents and young adults to serve as a basis for program development.Research Method – The study employed a quantitative approach using a descriptive survey design oriented towards a needs assessment. It was conducted in Babakan Sari Urban Village, Bandung City, involving 35 respondents aged 11–22 years selected through purposive sampling. Data were collected using a 20-item structured questionnaire with response formats tailored to the nature of the questions. Data were analyzed using frequencies, percentages, and a synthesis across components.Research Findings – The study produced a needs map covering social conditions, parenting styles and family communication, perceptions of reproductive health, peer relationships, and social and information environments. This synthesis was formulated into the Adolescent Reproductive Health Education Needs Framework (ARHENF), serving as an initial conceptual synthesis based on survey findings rather than an empirically validated framework.Research Conclusion – The needs analysis provides an empirical basis for understanding reproductive health education needs in alignment with the characteristics and life contexts of adolescents and young adults.Research Novelty/Contribution – The study's contribution lies in the integrated mapping of needs and their synthesis into the ARHENF, serving as a conceptual foundation for the development of reproductive health education programs.